1998
DOI: 10.1046/j.1365-2249.1998.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of murine macrophage-membrane proteins with components of the pathogenic fungusHistoplasma capsulatum

Abstract: The interaction of macrophage-membrane proteins and histoplasmin, a crude antigen of the pathogenic fungus Histoplasma capsulatum, was studied using murine peritoneal macrophages. Membrane proteins were purified via membrane attachment to polycationic beads and solubilized in Tris-HCl/SDS/DTT/glycerol for protein extraction; afterwards they were adsorbed or not with H. capsulatum yeast or lectin binding-enriched by affinity chromatography. Membrane proteins and histoplasmin interactions were detected by ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…The expression of lectins by pathogenic microorganisms has been correlated to the organism attachment and invasion to host tissues (Mendes-Giannini et al, 2000 ; Singh et al, 2011 ). Interestingly, Hc has components with lectin activity on the yeast surface that can bind to surface molecules on murine macrophages (Taylor et al, 1998 ; Duarte-Escalante et al, 2003 ). It has been shown that a lectin-like molecule plays a role in the binding to macrophage surface proteins suggesting that the specific receptor for histoplasmin components on macrophage could be an oligosaccharide–protein complex containing galactose (mainly β-anomer) as determinant, since enzymatic cleavage of galactosyl residues or a galactose N -acetyl- d -galactosamine compound reduced this interaction (Maldonado et al, 1994 , 1998 ; Taylor et al, 1998 ).…”
Section: Yeast Cell Surfacementioning
confidence: 99%
“…The expression of lectins by pathogenic microorganisms has been correlated to the organism attachment and invasion to host tissues (Mendes-Giannini et al, 2000 ; Singh et al, 2011 ). Interestingly, Hc has components with lectin activity on the yeast surface that can bind to surface molecules on murine macrophages (Taylor et al, 1998 ; Duarte-Escalante et al, 2003 ). It has been shown that a lectin-like molecule plays a role in the binding to macrophage surface proteins suggesting that the specific receptor for histoplasmin components on macrophage could be an oligosaccharide–protein complex containing galactose (mainly β-anomer) as determinant, since enzymatic cleavage of galactosyl residues or a galactose N -acetyl- d -galactosamine compound reduced this interaction (Maldonado et al, 1994 , 1998 ; Taylor et al, 1998 ).…”
Section: Yeast Cell Surfacementioning
confidence: 99%
“…Early studies showed that a 50-kDa cell wall protein from H. capsulatum yeast was able to bind laminin with high affinity, a process thought to be important in the initial stages of infection [100]. Later, a specific lectin-like interaction between H. capsulatum yeast and macrophage-membrane proteins was identified [101]. This lectin-like binding was initially thought to be specific for b-Gal residues; however, more recent studies have shown binding to human erythrocytes may be mediated through Sia [102].…”
Section: Histoplasma Capsulatummentioning
confidence: 99%
“…A lectinmediated interaction between H. capsulatum yeast and host cells has been considered, in which lectin activity is associated with a component present on the yeast cell surface. This lectin-like activity is specific to galactosylated surface molecules (mainly b-anomer) on murine macrophages (Taylor et al 1998;MendesGiannini et al 2000;Duarte-Escalante et al 2003). H. capsulatum yeast also has the ability to bind and agglutinate human erythrocytes through this lectin-like component (Taylor et al 2004).…”
Section: Discussionmentioning
confidence: 99%